Pengelompokkan Tingkat Pemahaman Kurikulum Berbasis KKNI Menggunakan Metode X-Means Clustering - Saeful Anwar; Nisa Dieanwati Nuris; Yudhistira Arie Wijaya (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
In Law Number 12 of 2012 concerning Higher Education in Article 35 Paragraph 2 explains that the development of PT curriculum refers to the National Higher Education Standards for every study program that develops noble, intellectual intelligence and skills. KKNI or the Indonesian National Qualification Framework brings together, equates, and combines the field of education with the field of training and work experience and conceptually the Indonesian National Qualification Framework (KKNI) is composed of six (6) main parameters consisting of science, knowledge, know-how, skills, affection, competency. From the results of clustering analysis or grouping using the x-means algorithm it is found that the parameters of science (A), knowledge (B), skill (D), and competency (F) respondents are more likely to answer understanding and are very understanding. In the know-how parameter (C) the tendency of respondents to answer is well understood, whereas for the affection parameter (E) respondents tend to answer between understanding and quite understand but is in contrast between cluster 0 and cluster 1.